Challenging Case Report: Reevaluating autism diagnosis in a 7-year-old girl - Nagar-Shimoni, Hagit; Leibovitch, Noa; Zilbershot Fink, Efrat; Cnaan, Yuval; Leitner, Yael (Frontiers in Psychiatry, 2026)
Diagnosing autism spectrum disorder (ASD) in verbally fluent, socially motivated children, particularly girls, remains challenging due to compensatory behaviors and masking. This case report follows a 7-year-old girl repeatedly referred to autism spectrum evaluation. Despite early developmental delays, attentional variability, and sensory sensitivities, initial community-based multidisciplinary assessment excluded ASD but did not resolve parental concerns. A second evaluation at the hospital-based developmental clinic included neurological and psychological assessments, revealing divergent impressions and prompting naturalistic peer-group observations. In these naturalistic settings, the girl demonstrated strong social interest, reciprocity, emotional expressiveness, and adaptability, with no repetitive behaviors or marked rigidity. Support was required for attention and frustration management, but overall social interaction quality was age-appropriate given her developmental profile. The final diagnosis ruled out ASD. The observed difficulties were instead attributed to below-average cognitive functioning, Attention Deficit Hyperactivity Disorder, language difficulties and immature socio-emotional development. This case highlights the value of integrating longitudinal, naturalistic peer-group observations with standardized tools to provide ecologically valid insights into adaptive functioning. Such methods are particularly useful in complex diagnostic cases and align with recent calls to refine procedures for girls with social difficulties. In the present case, accurate diagnostic clarification required sustained multidisciplinary teamwork, clear communication with the parents, and the incorporation of naturalistic peer-group observation alongside standardized assessment tools.